Dans quelle mesure la capacité d’absorption favorise le transfert des connaissances aux PME dans les alliances stratégiques ? Proposition d’un modèle explicatif - ZARKI , Nabil; EL HAMMOUMI , Ahmed (Revue Internationale du Chercheur, 2021)
Absorption capacity is an organizational objective and a functional challenge for humain resource manager which must act on two fundamentals elements to get it: the skills, and the motivation of the staff to acquire new knowledge, which can be cultivated through communication. Internal and performance-based compensation. Therefore, absorption capacity is an important issue for the Moroccan State as for local companies, the process of acquiring knowledge and know-how is the main objective of these companies to increase their competitiveness and the added value of their products. The goal of our research is to understand the influence of absorptive capacity on the process of transfer of knowledge and skills in asymmetric strategic alliances. After having given his concept, we will specify these elements, in order to measure it.